The Multilateral Trading System: Problems of Harmonization of The Multilateral and Regional Regulation of Trade and Economic Relations - Yuri Ilyich Chentukov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article analyzes the development of global and regional economic integration in modern conditions. The authors identified and characterized the main components of a transparent mechanism for the development of regional trade agreements in the multilateral trading system.